2015
DOI: 10.5114/pm.2015.50000
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic disorders in menopause

Abstract: Metabolic disorders occurring in menopause, including dyslipidemia, disorders of carbohydrate metabolism (impaired glucose tolerance – IGT, type 2 diabetes mellitus – T2DM) or components of metabolic syndrome, constitute risk factors for cardiovascular disease in women. A key role could be played here by hyperinsulinemia, insulin resistance and visceral obesity, all contributing to dyslipidemia, oxidative stress, inflammation, alter coagulation and atherosclerosis observed during the menopausal period. Undiagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
89
1
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(103 citation statements)
references
References 51 publications
1
89
1
10
Order By: Relevance
“…It is possible that the findings are associated with changes in reproductive hormones, such as estrogen, follicle stimulating hormone (FSH), and luteinizing hormone (LH) as well as melatonin secretion after entering menopause [15,16]. These changes lead to metabolic changes such as increases in appetite, dietary consumption, and adiposity as well as alternation in energy homeostasis [19,20,21]. A study of a population of Brazilian females reported that postmenopausal women with higher BMI levels had high levels of TG and FG but low levels of HDL-C [22].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the findings are associated with changes in reproductive hormones, such as estrogen, follicle stimulating hormone (FSH), and luteinizing hormone (LH) as well as melatonin secretion after entering menopause [15,16]. These changes lead to metabolic changes such as increases in appetite, dietary consumption, and adiposity as well as alternation in energy homeostasis [19,20,21]. A study of a population of Brazilian females reported that postmenopausal women with higher BMI levels had high levels of TG and FG but low levels of HDL-C [22].…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, after an individual evaluation, hormone replacement therapy was recommended (44), which could have a positive effect on lipids by reducing total and LDL cholesterol and by slightly increasing HDL levels, as demonstrated in a meta-analysis (45).…”
Section: Metabolic Syndrome In Menopausal Womenmentioning
confidence: 99%
“…It also increases circulating estrogen and improves glucose and lipid metabolism. So far, exercise is still the first choice for menopause women to alleviate symptoms due to metabolic disorders (Stachowiak, Pertynski, & Pertynska‐Marczewska, 2015; Sternfeld et al, 2014). Moreover, exercise increases the synthesis of local estrogen (Aizawa et al, 2011) and boosts the level of estrogen and aromatase in the muscle (Shi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%